Contextualizing of Technology Issues in Anthropology Learning: Efforts to Strengthen Social Concern in The Digital Era - Lisna Sandora; Nissya Febrizani (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
Anthropology learning in higher education is often constrained by theoretical instruction and limited contextual engagement, reducing students’ opportunities to connect anthropological concepts with contemporary social realities. This study aimed to develop and assess the feasibility of a Science, Technology, and Society (STS)-based Anthropology learning model to strengthen students’ social concern in Islamic higher education. Using a Research and Development design with an evaluative orientation, the study was conducted through three stages: needs analysis, model development, and expert validation. Data were collected through classroom observation, Semester Learning Plan analysis, structured interviews, social concern questionnaires, documentation, and expert validation sheets. Quantitative data were analyzed using descriptive statistics, while qualitative data were examined through thematic analysis. The findings show that Anthropology learning requires a more contextual, participatory, and reflective structure that enables students to identify technology-related social issues, analyze them through anthropological concepts, and reflect on their ethical and social implications. The developed model consists of issue identification, concept formation, field application, social concern development, reporting of findings, and assessment. Its supporting products include a model book, lecturer guidebook, and student guidebook. The novelty of this study lies in extending the STS approach into Anthropology learning by positioning technology issues as social and cultural phenomena rather than merely technical matters. The model offers a structured pedagogical framework for linking conceptual understanding, field observation, ethical reflection, and social responsibility. Further classroom-based testing is recommended to examine its effectiveness in improving students’ social concern across broader higher education contexts.